Organic Solvent Tolerant Lipases and Applications. (2nd February 2014) - Sharma, Shivika; Kanwar, Shamsher S.
Abstract : Lipases are a group of enzymes naturally endowed with the property of performing reactions in aqueous as well as organic solvents. The esterification reactions using lipase(s) could be performed in water-restricted organic media as organic solvent(s) not only improve(s) the solubility of substrate and reactant in reaction mixture but also permit(s) the reaction in the reverse direction, and often it is easy to recover the product in organic phase in two-phase equilibrium systems. The use of organic solvent tolerant lipase in organic media has exhibited many advantages: increased activity and stability, regiospecificity and stereoselectivity, higher solubility of substrate, ease of products recovery, and ability to shift the reaction equilibrium toward synthetic direction. Therefore the search for organic solvent tolerant enzymes has been an extensive area of research. A variety of fatty acid esters are now being produced commercially using immobilized lipase in nonaqueous solvents. This review describes the organic tolerance and industrial application of lipases. The main emphasis is to study the nature of organic solvent tolerant lipases. Also, the potential industrial applications that make lipases the biocatalysts of choice for the present and future have been presented.